Análisis del Conocimiento, Actitudes y Prácticas del uso de Elementos de Protección en el Personal de la salud de la Universidad Antonio Nariño sede Villavicencio en el año 2023 (2023)
The use of Personal Protective Elements by the health services team to reduce crosscontamination and the spread of diseases is becoming increasingly important. The COVID-19 pandemic is an example of this importance, which is why this research focuses on identifying: the knowledge, attitudes, and practices in the use of PPE in students and dentists at the Antonio Nariño University, Villavicencio campus. , during the year 2023. To achieve this objective, an observational, qualitative-quantitative, cross-sectional study was carried out, in which 79 people participated, including students, professionals and dental assistants, to whom two information collection instruments were applied (survey and a data collection format), validated by experts, with reliability determined under Cronbach's alpha (82.3%). The results indicate that 46.8% acceptable levels of knowledge in the majority of participants, excellent levels in both attitudes (98.7%), and good levels in PPE use practices (54.4%) by students and dentists in the clinic of the Antonio Nariño University headquarters in Villavicencio. In conclusion, despite the acceptable level of knowledge about the use of Personal Protective Equipment (PPE) in the dental clinic, it should be highlighted that the staff observed demonstrate a good level of practice in its use in their work and an excellent level in the attitude towards the use of PPE. Keywords: Knowledge, Attitudes, Practices, Personal Protection Elements.